Artificial Intelligence in Language Teaching: Adaptive Tutors, Grammar Checkers, and the Future of Personalized Learning - Shirinova, Komilaxon Baxtiyor qizi (The Lingua Spectrum, 2026)
Artificial Intelligence (AI) has rapidly become a central force in reshaping education, particularly in language teaching. This article examines the application of AI-powered tools such as adaptive tutors, grammar checkers, and speech recognition systems in language learning contexts. Using the IMRAD structure, the paper explores current developments, evaluates their effectiveness, and discusses both opportunities and challenges. The study highlights how AI promotes personalization, learner autonomy, and accessibility while also emphasizing the continuing importance of teachers in guiding meaningful communication and critical thinking.The findings suggest that AI should be integrated as a supportive educational partner rather than viewed as a replacement for human instruction.